Respon Petani Terhadap Media Penyuluhan pada Program Pekarangan Pangan Lestari Menggunakan Analisis Structural Equation Modeling - Rudiyanto Doyok; Ana Arifatus Sa'diyah; Ahmad Yusuf Kholili (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2023)
Pekarangan Pangan Lestari (P2L) is an activity carried out by community groups that jointly work on their yard as a source of food in a sustainable manner to increase availability, accessibility, and utilization, as well as income. There are three indicators that influence farmers' response to extension media, namely cognitive, affective and psychomotor. The purpose of this study was to analyze the factors that influence Farmers' Responses to Extension Media in the Sustainable Food Yard Program (P2L) and to analyze the level of Farmers' Responses to Extension Media in the Sustainable Food Yard Program (P2L). The research was conducted in Juwet Manting Hamlet, Parangargo Village, Wagir District, Malang Regency. Respondents were determined as many as 39 people from a total population of 65 people. Data were analyzed using Structural Equation Modeling (SEM). The results showed that the factors that influence the response of farmers to media extension in the Sustainable Food Program (P2L) are interest which is an affective variable and the level of response of farmers to media extension in the Sustainable Food Program (P2L) is high.